Novel Insights Into Monogenic Obesity Syndrome Due to INPP5E Gene Variant: A Case Report of a Female Patient - Drole Torkar, Ana; Avbelj Stefanija, Magdalena; Bertok, Sara; Trebušak Podkrajšek, Katarina; Debeljak, Maruša; Stirn Kranjc, Branislava; Battelino, Tadej; Kotnik, Primož (Frontiers in Endocrinology, 2021)
A Caucasian girl with consanguineous parents presented with early severe obesity and retinal dystrophy. A novel, homozygous gene truncating variant (c.1897C>T) in the INPP5E gene confirmed the diagnosis of MORMS (OMIM #610156). A novel clinical finding in the presented syndrome is progressive cone-rod type retinal dystrophy diagnosed at the age of four months that progressed in the 1st decade of life. Severe obesity, insulin resistance with hyperinsulinism, and impaired glucose tolerance developed alongside other components of the metabolic syndrome - dyslipidemia, arterial hypertension, and obstructive hypopnea in sleep. At the age of 14 years, primary amenorrhea persists. The patient is managed by regular nutritional advice, metformin, antihypertensive medication, and non-invasive respiratory support during sleep. Differential diagnosis of this rare entity is discussed in extend.